2017
DOI: 10.3892/mco.2017.1456
|View full text |Cite
|
Sign up to set email alerts
|

En bloc resection, intraoperative extracorporeal irradiation and re‑implantation of involved bone for the treatment of limb malignancies

Abstract: Abstract. Reconstruction of the defect following limb-sparing resection of malignant bone tumors is controversial and extremely challenging. Extracorporeal irradiation (ECI) and re-implantation have been used for limb salvage surgery for patients, with major advantages, including biological reconstruction, ready availability and preservation of bone stock, over replacement with a megaprosthesis. The purpose of the present study was to present our experience and details of all patients treated with this surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Functions and longevity rates were better in spite of high re-surgery (39.1%) and complications (47.8%). 6 Other studies have also shown treatment by ECRT. 7 Ewing's sarcoma (33%) and osteosarcoma (67%) were commonly found in our study, consistent with known numbers found in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…Functions and longevity rates were better in spite of high re-surgery (39.1%) and complications (47.8%). 6 Other studies have also shown treatment by ECRT. 7 Ewing's sarcoma (33%) and osteosarcoma (67%) were commonly found in our study, consistent with known numbers found in other studies.…”
Section: Discussionmentioning
confidence: 97%